High Expression Levels of Foxp3 and VISTA in Advanced Human Gliomas and Impact on Patient’s Prognosis - Ghouzlani, Amina; Kandoussi, Sarah; Rafii, Soumaya; Lakhdar, Abdelhakim; Badou, Abdallah (Archives of Clinical and Biomedical Research, 2020)
Gliomas are considered the most malignant cancers of the body. Despite the advances in cancer therapy, this type of tumor continues to progress and be more aggressive. In human gliomas, anti-tumor T cell responses are inhibited through induction of local and systemic immunosuppression. Cancer immunotherapy using immune checkpoint blockade has made a great stride in mending patient’s clinical outcome for multiple types of cancers. However, many studies reported that treatment of glioblastoma patients with anti-CTLA4 and anti-PD-1 has no survival benefit compared to standard chemotherapy. The aim of this study was to investigate the role of regulatory T cells as well as VISTA in the suppression of immune cell functions within glioma microenvironment, using molecular biology and bioinformatics approaches. Foxp3 and VISTA mRNA expression were assessed in human glioma patients at different grades using 2 independent cohorts, a set of 20 Moroccan patients, and a series of 667 patients from TCGA. The expression of Foxp3, a transcription factor specific for Treg cells, and VISTA, a newly identified immune checkpoint molecule, significantly correlated with gliomas grading and with the most aggressive histological type. Indeed, this expression was associated with bad overall survival of patients. Thus, finding new strategies for blocking VISTA on Treg cells in the tumor microenvironment could be beneficial in stopping the tumor progression. Our study highlighted a correlation between high levels of VISTA expression and Foxp3 with a bad prognosis in glioma patients. VISTA expression in Treg cells might be involved in glioma progression and could be considered as a possible new therapeutic target especially in glioblastoma.